2020
DOI: 10.1371/journal.pone.0244943
|View full text |Cite
|
Sign up to set email alerts
|

Biology of a putative male aggregation-sex pheromone in Sirex noctilio (Hymenoptera: Siricidae)

Abstract: A putative male-produced pheromone has recently been described for the global pest of pines, Sirex noctilio, but field-activity has not been demonstrated. This study aimed to investigate the pheromone biology of S. noctilio in more detail. Specifically, we i) analysed effluvia and extracts for additional compounds by gas chromatography coupled with electro-antennographic detection (GC-EAD), mass spectrometry (GC-MS) and two dimensional time of flight mass spectrometry (GC X GC TOF MS), ii) conducted dose-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…Meanwhile, studies have shown that release and storage of aggregated pheromones in S. noctilio may originate from the leg tendon gland of the hind legs, which is a centrally controlled storage. The leg tendon gland is a hollow reservoir starting in the femur and running down to the unguitractor plate, manubrium and arolium structures situated at the end of the clamp [ 48 ]. With a similar structure such as the tracer pheromone released by ant Crematogaster , which comes from the tibial tendon gland of their hind legs [ 60 ], females in Ascogaster reticulatus release ( Z )-9-hexadecenal as a sex pheromone from the hind legs [ 61 ]; male Polistes dominulus are thought to release a lek-formation pheromone from their legs [ 62 ]; foragers in the stingless bee Melipona seminigra use a pheromone from the hind leg tendon gland to mark their food sites [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, studies have shown that release and storage of aggregated pheromones in S. noctilio may originate from the leg tendon gland of the hind legs, which is a centrally controlled storage. The leg tendon gland is a hollow reservoir starting in the femur and running down to the unguitractor plate, manubrium and arolium structures situated at the end of the clamp [ 48 ]. With a similar structure such as the tracer pheromone released by ant Crematogaster , which comes from the tibial tendon gland of their hind legs [ 60 ], females in Ascogaster reticulatus release ( Z )-9-hexadecenal as a sex pheromone from the hind legs [ 61 ]; male Polistes dominulus are thought to release a lek-formation pheromone from their legs [ 62 ]; foragers in the stingless bee Melipona seminigra use a pheromone from the hind leg tendon gland to mark their food sites [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only Z3D was identified from the S. noctilio Chinese population, and the peak of Z3D release occurred from 11:00–12:00 for two-day-old individuals, which can elicit antennal response consistently in our GC-EAD assays ( Figure S1 ) [ 45 , 46 , 47 ]. Two putative male aggregation pheromones in S. noctilio that have not been validated in field-activity were identified as ( Z )-3-octen-ol and ( Z )-3-dodecen-ol; these two new substances were not identified in our previous experiments [ 48 ]. This pheromone-related research indicated that Z3D plays an important role in regulating the behavioral rhythm of woodwasps.…”
Section: Introductionmentioning
confidence: 99%
“…The male swarms of S. noctilio contrast with the definition of the classical lek‐forming species, in which males compete for territories that contain no resources vital to females, except copulation and mating (Thornhill & Alcock, 1983; Bradbury & Gibson, 1983; Shelly & Whittier, 1997). However, in support of the lek hypothesis, Allison et al (2021) reported the attraction of females to traps baited with only dead males, and Guignard et al (2020) discovered two electroantennographically detected (EAD) compounds – ( Z )‐3‐octenol and ( Z )‐3‐dodecenol – which are released from the hind legs of males, and elicited antennal responses from both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…with only dead males, and Guignard et al (2020) discovered two electroantennographically detected (EAD) compounds -(Z)-3-octenol and (Z)-3-dodecenol -which are released from the hind legs of males, and elicited antennal responses from both sexes.…”
mentioning
confidence: 99%
“…Field studies have reported that males aggregate at the top of pine trees to form leks and females are attracted to these for mating 25 – 27 . A male specific putative pheromone released from the sexually dimorphic hind legs has been described 28 . We refer to this as a putative pheromone because although attraction was observed in the lab 29 , it was inactive in field trials 30 suggesting that other sensory modalities than olfaction could play an important role in mate attraction.…”
Section: Introductionmentioning
confidence: 99%